2020
DOI: 10.1002/app.48979
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of low‐density polyethylene with prooxidant and photocatalyst

Abstract: Low‐density polyethylene (LDPE) composite films with trisilver phosphate (Ag3PO4) and cadmium selenide (CdSe) particles as photocatalysts and manganese stearate as prooxidant were prepared. The film samples were irradiated under UV and visible light and their photodegradation were evaluated using Fourier‐transform infrared spectroscopy, scanning electron microscopy, thermogravimetric analysis, and differential scanning calorimetry. The carbonyl index of the photocatalyst containing samples was very higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…On the other hand, the PE_ONM film, with higher reduction of , higher increase in COi and Vi, shows extreme brittleness, clear in micrographic observation after 144 h of exposure. In another work [ 22 ], evaluating the photodegradation of PE_ONM with pro-oxidants and photocatalysts, morphological changes compatible with those obtained in this study were found, with changes as clearer the higher the degradation rate observed for the polymer.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…On the other hand, the PE_ONM film, with higher reduction of , higher increase in COi and Vi, shows extreme brittleness, clear in micrographic observation after 144 h of exposure. In another work [ 22 ], evaluating the photodegradation of PE_ONM with pro-oxidants and photocatalysts, morphological changes compatible with those obtained in this study were found, with changes as clearer the higher the degradation rate observed for the polymer.…”
Section: Resultssupporting
confidence: 86%
“…Processing PE with pro-oxidant additives has been an option to favor the abiotic degradation of macromolecules, by photooxidation and thermooxidation, leading to the production of lower molar mass oxygenated fragments. In a second stage of the degradation process, these fragments are assimilated by microorganisms such as fungi, bacteria and algae, constituting the biotic degradation [ 4 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. When processed with such additives, PE is called oxo-biodegradable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical-oxidative degradation of polymer samples is usually accompanied by the appearance of unsaturated bonds and various carbonyl groups by which the progression of degradation increases [ 70 ]. Two major observations—the formation of C=O (2000–1500 cm −1 ) and O-H groups in (4000–3000 cm −1 ) can also be found in the FTIR spectrum of polyolefin and other polymers [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…An increase in the crystallinity and carbonyl index was also observed after exposure of LDPE films to UV irradiations ( Gharehdashli et al, 2020 ). Ranjan et al indicated that the photodegradation of LDPE is faster in the air than its counterparts (double distilled water, two salt solutions with variable ionic strengths), under UV irradiation for 90 days.…”
Section: Mechano-thermo-photo Irradiative and Green Chemical (Pre)trementioning
confidence: 95%